2017
DOI: 10.1002/2017gl073596
|View full text |Cite
|
Sign up to set email alerts
|

A new heat flux model for the Antarctic Peninsula incorporating spatially variable upper crustal radiogenic heat production

Abstract: A new method for modeling heat flux shows that the upper crust contributes up to 70% of the Antarctic Peninsula's subglacial heat flux and that heat flux values are more variable at smaller spatial resolutions than geophysical methods can resolve. Results indicate a higher heat flux on the east and south of the Peninsula (mean 81 mW m−2) where silicic rocks predominate, than on the west and north (mean 67 mW m−2) where volcanic arc and quartzose sediments are dominant. While the data supports the contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 62 publications
8
66
0
Order By: Relevance
“…However, the higher differences are concentrated in the central part of the Antarctic Peninsula. A local measurement of 88 mW/m 2 fits very well with our model (92 mW/m 2 ), while it almost double the one obtained by Burton‐Johnson et al ().…”
Section: Discussion and Model Validationsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the higher differences are concentrated in the central part of the Antarctic Peninsula. A local measurement of 88 mW/m 2 fits very well with our model (92 mW/m 2 ), while it almost double the one obtained by Burton‐Johnson et al ().…”
Section: Discussion and Model Validationsupporting
confidence: 89%
“…The Antarctic Peninsula shows higher spatial variability and amplitude in our study, while that is not the case in previous proposed maps. A recent model from the Antarctic Peninsula (Burton‐Johnson et al, ) based on heat production values from rock samples and the crustal model by An et al () has some resemblance with our map in the same region in terms of the distribution of heat flux values. Elevated heat flux is found in the eastern part of the Antarctic Peninsula, while low values are in the west and northern tip in both maps.…”
Section: Discussion and Model Validationsupporting
confidence: 78%
“…Furthermore, geophysical models use simple layered crustal models (one‐ to two‐layered crust) that field studies of heat production heterogeneity have repeatedly shown are not geologically realistic (Burton‐Johnson et al, ; Carson et al, ; Hasterok et al, ; Sandiford et al, ). The models apply either constant thermal conductivity through a single crustal layer and assume laterally uniform crustal heat production (An et al, ), or an exponential relationship of decreasing heat production with depth (Martos et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…GHF has been inferred for some regions of the WAIS from the distribution of subglacial water (Schroeder et al, ; Siegert & Dowdeswell, ). Due to the paucity of observations, the GHF distribution used in ice sheet models typically falls within a relatively narrow range and has low spatial variability, based on geological or remotely sensed properties of the underlying lithosphere (An et al, ; Burton‐Johnson et al, ; Fox Maule et al, ; Pollack et al, ; Shapiro & Ritzwoller, ). GHF models of West Antarctica are inconsistent with one another in both magnitude and distribution (Figure S1 in the supporting information), suggesting that GHF is not well constrained.…”
Section: Introductionmentioning
confidence: 99%